The effect of montages of transcranial alternating current stimulation on occipital responses—a sham-controlled pilot study - Wang, Jingying; Choi, Kai Yip; Thompson, Benjamin; Chan, Henry Ho Lung; Cheong, Allen Ming Yan (Frontiers in Psychiatry, 2024)
Transcranial alternative current stimulation (tACS) is a promising non-invasive technique to improve brain functions. However, owing to various stimulation parameters in the literature, optimization of the stimulation is warranted. In this study, we aimed to compare the effect of tACS electrode montages on occipital responses. Ten healthy young adults took part in three montage-sessions (i.e., Oz-Cz, Oz-cheek, and Sham) with 20-minute 2-mA alpha-tACS. Pattern-reversal-visual-evoked-potentials (VEP) were measured before tACS (T0), immediately after (T20), and 20minutes (T40) after tACS. Normalized changes in time-domain features (i.e., N75, P100 amplitudes and P100 latency) and frequency-domain features (i.e., power spectral density in alpha [PSDα] and beta [PSDβ] bands) were evaluated. In contrast to our hypothesis, the occipital response decreased immediately (T20) after receiving the 20-minute tACS in all montages in terms of P100 amplitude (p=0.01). This reduction returned to baseline level in Oz-cheek and Sham conditions but sustained in the Oz-Cz condition (T40, p=0.03) after 20minutes of tACS. The effects on N75 amplitude and P100 latency were statistically insignificant. For the spectral analysis, PSDα and PSDβ were significantly increased after tACS at T20, in which the effect sustained to T40. However, there was no differential effect by montages. There was no significant difference in the occurrence of sensations across the montages. The effectiveness of the blinding is supported by the participants' rate of correct guessing. The current study revealed an immediate inhibitory effect of tACS regardless of the montages. This inhibitory effect sustained in the Oz-Cz montage but faded-out in other montages after 20minutes.